Long‐term outcomes of pacemaker implantation in children with univentricular versus complex biventricular surgical repair. Issue 2 (12th February 2023) - Spentzou, Georgia; Taylor, Luke; Zhang, Yiyan; D'Udekem, Yves; Zannino, Diana; Davis, Andrew; Pflaumer, Andreas
Abstract: Objective: Pacing in a univentricular circulation has been associated with worsened outcomes. We investigated the long‐term outcomes of pacing in children with a univentricular circulation compared to a complex biventricular circulation. We also identified predictors of adverse outcomes. Methods: A retrospective study of all children with major congenital heart disease who underwent pacemaker implantation under the age of 18 years between November 1994 and October 2017. Results: Eighty‐nine patients were included; 19 with a univentricular and 70 with a complex biventricular circulation. A total of 96% of pacemaker systems were epicardial. Median follow up was 8.3 years. The incidence of adverse outcome was similar between the two groups. Five (5.6%) patients died and two (2.2%) underwent heart transplantation. Most adverse events occurred within the first 8 years after pacemaker implantation. Univariate analysis identified five predictors of adverse outcomes in the patients in the biventricular but none in the univentricular group. The predictors of adverse outcome in the biventricular circulation were a right morphologic ventricle as the systemic ventricle, age at first congenital heart disease (CHD) operation, number of CHD operations, and female gender. The nonapical lead position was associated with a much higher risk of an adverse outcome. Conclusions: Children with a pacemaker and a complex biventricular circulation have similar survival to the ones with a pacemaker and a univentricular circulation. The only modifiable predictor was the epicardial lead position on the paced ventricle, emphasizing the importance of apical placement of the ventricular lead.